Study of Plant Community and Utilization in the Ban Chan Public Cemetery Forest at Thung Kula Subdistrict Municipality, Suwannaphum District, Roi Et Province - นาคะวงศ์ สุกัญญา; ชาแท่น ผู้ช่วยศาสตราจารย์ ดร.วรรณชัย; พร้อมพรม ผู้ช่วยศาสตราจารย์ ดร.วิลาวัณย์ (Journal of Food Health and Bioenvironmental Science, 2017)
The study of the plant community and utilization in the Ban Chan public cemetery forest at Thung Kula subdistrict municipality, Suwannaphum district, Roi Et province was conducted during May 2014-May 2015 by exploration, collection and interviewing folk herbalists. The results showed that 64 species, 55 genera from 35 families, were found. Among these, Fabaceae was the richest in number of species (7 species) and the second richest was Rubiaceae (5 species). These plants were classified into 24, 30 and 40 species of tree, sapling and seedling, respectively. The trees had a diversity index (H) of 2.75, a evenness index (J) of 0.86, and a species diversity (D) of 15.67. Dipterocarpus intricatus Dyer had the highest importance value index (52.16 species). The saplings had a diversity index of 2.91, a evenness index of 0.84 and a species diversity of 17.66. Cratoxylum formosum had the highest importance value index of 45.82. The seedlings had a diversity index of 3.16, a evenness index of 0.85 and a species diversity of 23.64. Sixtyone species were used by villagers, divided into 5 groups. Two species was used for folk custom and culture. Thirty-eight species were used as herbal medicinal plants. Thrity-five species were used as food. Eighteen species were used for materials science and local technology and twelve species were used as fuel materials. Voucher specimens were deposited in the Department of Biology, Faculty of Science, Mahasarakham University.